2000
DOI: 10.1093/ps/79.9.1345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo administration of insulin-like growth factor-I on compositionand mechanical properties of chicken bone

Abstract: The influence of in ovo administration of insulin-like growth factor-I (IGF-I) on long bone growth (tibiae and femora) of 42-d-old broiler chickens was investigated. Eggs were divided into three groups: uninjected control, vehicle-injected control, and recombinant human (rh) IGF-I. Eggs were injected once with 100 microL vehicle (10 mM acetic acid and 0.1% BSA) per embryo or vehicle containing 100 ng rh IGF-I/100 microL per embryo (n = 555 eggs total) on Days 1, 2, 3, or 4 of embryonic development. Males had g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…This suggests that every component of hypothalamic-pituitary-gonad axis could be the action site for IGF-I through endocrine and paracrine systems [41]. However, in agreement with previous publications [16], [21], [22], IGF-I impact was restricted to the male chicks. This indicates the presence of very strong interaction between sexual hormones and IGF-I.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that every component of hypothalamic-pituitary-gonad axis could be the action site for IGF-I through endocrine and paracrine systems [41]. However, in agreement with previous publications [16], [21], [22], IGF-I impact was restricted to the male chicks. This indicates the presence of very strong interaction between sexual hormones and IGF-I.…”
Section: Discussionsupporting
confidence: 89%
“…We evaluated the simultaneous and separate effects of these two compounds on female-to-male sex reversal and body weight on the Day 1 and 42 of production as well as the hatching traits. Strong similarity of human and chicken IGF-I protein sequence [27], [28], very high affinity of rhIGF-I to the chicken IGF-I receptors [29], and successful usage of rhIGF-I for improving chicken body weight [16], [22] persuaded us to use rhIGF-I in the current study. We showed that IGF-I combination with Fadrozole could enhance female-to-male sex reversal, shorten hatching time, and increase chicken body weight.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Vaccine manufacturers today are desiring to develop new products that can be injected in ovo to enhance vaccine efficacy and to improve broiler embryogenesis and posthatch performance. Nutrients and other metabolic compounds for in ovo injection, such as amino acids, carbohydrates, vitamins, stimulants, and hormones, are under investigation (Gore and Qureshi, 1997;Johnston et al, 1997;Henry and Burke, 1999;Kocamis et al, 1999Kocamis et al, , 2000Ohta et al, 1999;Jochemsen and Jeurissen, 2002;Tako et al, 2004;Uni et al, 2005;Foye et al, 2006;Kadam et al, 2008;Zhai et al, 2008;Keralapurath et al, 2010a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the traditional method of broiler vaccination, in ovo injection offers a less stressful, faster, and more uniform delivery of vaccines and nutrient mixtures to developing embryos (Williams, 2007). Included among the various embryological and physiological studies that are made possible by in ovo injection technology are investigations concerning the effects of substances such as amino acids (Ohta et al, 1999;Kadam et al, 2008), carbohydrates (Tako et al, 2004;Uni et al, 2005;Zhai et al, 2011c), electrolyte solutions (McGruder et al, 2011), hormones (Henry and Burke, 1999;Kocamis et al, 1999Kocamis et al, , 2000, nucleotides (Dalloul et al, 2005), stimu-lants (Zhai et al, 2008;Keralapurath et al, 2010), and vitamins (Gore and Qureshi, 1997;Bhanja et al, 2007).…”
Section: Introductionmentioning
confidence: 99%